Plasmodium falciparum parasites overexpressing farnesyl diphosphate synthase/geranylgeranyl diphosphate synthase are more resistant to risedronate - Heloisa B Gabriel; Mauro F Azevedo; Emília A Kimura; Alejandro M Katzin (Memorias do Instituto Oswaldo Cruz, 2018)
Farnesyl diphosphate synthase/geranylgeranyl diphosphate synthase (FPPS/GGPPS) is a key enzyme in the synthesis of isoprenic chains. Risedronate, a bisphosphonate containing nitrogen (N-BP), is a potent inhibitor of blood stage Plasmodium. Here, we show that P. falciparum parasites overexpressing FPPS/GGPPS are more resistant to risedronate, suggesting that this enzyme is an important target, and bisphosphonate analogues can be used as potential antimalarial drugs.